Achieving SDGs Targets as a Basis for Economic Area Development in Bone Bolango Regency - Juliana Juliana; Yuniarti Koniyo; Citra Panigoro; Muhammad Rizq Gobel (International Journal of Economics and Management Research, 2024)
The relatively high potential for natural wealth has apparently not been able to overcome the problem of poverty in the Bone Bolango area. The problem of poverty does not only occur in Bone Bolango district but is still a national problem. This research aims to determine the achievement of SDGs targets as the basis for economic development in Bone Bolango Regency. This research is a quantitative descriptive study that uses expert respondents who are related to or know directly the SDGs achievement indicators for Bone Bolango district. Data analysis uses procedure hierarchy analysis (AHP) using expert choice 11 software. The results of the research show that there are six indicators that are problems in Bone Bolango district based on the SDGs achievement categories. Based on the results of the analysis of the answers given by respondents, the values obtained based on importance are: 1) eliminating extreme poverty (0.368), 2) reducing the percentage of poverty (0.240), 3) reducing the percentage of poverty based on gender and age (0.223), 4 ) increasing the proportion of women in parliament (0.075), 5) increasing GDP per capita (0.054), and 6) increasing the tax to GDP ratio (0.040). Achieving the SDGs indicator targets which is a problem in Bone Bolango Regency requires support, so there are five aspects assessed in this research, namely regulatory support, RPJMD priorities, institutional support, budget support and partnerships.